THE EFFECT OF ENGAGE, STUDY, ACTIVATE (ESA) METHOD TO WRITING RECOUNT TEXT IN EIGHT GRADES OF MTSN 1 PONTIANAK - Yokie Prasetya Dharma (STKIP Persada Khatulistiwa Sintang, 2016)
The objectives in this research are; to find out whether there is significant difference in writing skill between the students who are taught by using ESA and those who are taught without using ESA. This research is an experimental research which held at MTs N 1 Pontianak, West Kalimantan. The research subjects are eight grade students. There are two groups in this research those are experimental group and control group, which class VIII B as the experimental group, that was taught by using Engage Study Activate (ESA) and class VIII A as the control group that was taught without using ESA. The mean score of the posttest in the experimental group is higher than pretest 50.60 > 35.93 and the mean score of the posttest in the control group is higher than pretest 43.27 > 40.67. It shows that the mean score of the posttest in the experimental group is higher than posttest of the control group 50.60 > 35.93. The result of t-test shows the result of p value is lower than the significant level .00 < .05 and t-test is higher than t table 5.934 > 2.045. therefore, the hypothesis is accepted. There is significant difference of writing recount text between the students who are taught using ESA and the students who are taught without using ESA of the Eight Grades Students of MTS N 1 Pontianak. Keywords: Engage Study Activate (ESA), Writing Recount Text, Effect.